Sexual dimorphism in chimpanzee (Pan troglodytes schweinfurthii) and human age-specific fertility. Issue 144 (July 2020) - Muller, Martin N.; Blurton Jones, Nicholas G.; Colchero, Fernando; Thompson, Melissa Emery; Enigk, Drew K.; Feldblum, Joseph T.; Hahn, Beatrice H.; Langergraber, Kevin E.; Scully, Erik J.; Vigilant, Linda; Walker, Kara K.; Wrangham, Richard W.; et al.
Abstract: Across vertebrates, species with intense male mating competition and high levels of sexual dimorphism in body size generally exhibit dimorphism in age-specific fertility. Compared with females, males show later ages at first reproduction and earlier reproductive senescence because they take longer to attain adult body size and musculature, and maintain peak condition for a limited time. This normally yields a shorter male duration of effective breeding, but this reduction might be attenuated in species that frequently use coalitionary aggression. Here, we present comparative genetic and demographic data on chimpanzees from three long-term study communities (Kanyawara: Kibale National Park, Uganda; Mitumba and Kasekela: Gombe National Park, Tanzania), comprising 581 male risk years and 112 infants, to characterize male age-specific fertility. For comparison, we update estimates from female chimpanzees in the same sites and append a sample of human foragers (the Tanzanian Hadza). Consistent with the idea that aggressive mating competition favors youth, chimpanzee males attained a higher maximum fertility than females, followed by a steeper decline with age. Males did not show a delay in reproduction compared with females, however, as adolescents in both sites successfully reproduced by targeting young, subfecund females, who were less attractive to adults. Gombe males showed earlier reproductive senescence and a shorter duration of effective breeding than Gombe females. By contrast, older males in Kanyawara generally continued to reproduce, apparently by forming coalitions with the alpha. Hadza foragers showed a distinct pattern of sexual dimorphism in age-specific fertility as, compared with women, men gained conceptions later but continued reproducing longer. In sum, both humans and chimpanzees showed sexual dimorphism in age-specific fertility that deviated from predictions drawn from primates with more extreme body size dimorphism, suggesting altered dynamics of male-male competition in the two lineages. In both species, coalitions appear important for extending male reproductive careers.